Current Status of Detection Technologies for Indoor Hazardous Air Pollutants and Particulate Matter - Yuhan Wang; Bingquan Wang; Rui Wang (Aerosol and Air Quality Research)
Abstract The application of modern gaseous pollutant detection techniques to monitor harmful gases and particulate matter in the indoor environment can effectively control air pollution and reduce accidents. Accurate, timely and economical monitoring of indoor concentrations of harmful gases and particulate matter in industrial production processes is still a great challenge. In recent years, there has been a gradual increase in research on detection methods for harmful gases and particulate matter. A number of researchers have published reviews of research on detection methods for hazardous gases, which are generally organized in terms of the detection of specific hazardous gases. In order to provide a more comprehensive overview of the latest research advances in detection methods for hazardous gases and particulate matter, this paper provides a categorized summary of research on detection methods for nitrogen dioxide, sulfur dioxide, hydrogen sulfide, formaldehyde, methane, and particulate matter. Through a comprehensive analysis of various detection methods, this paper discusses the current research progress of detection technology of indoor harmful gases and particulate matter, which is of great significance for timely and accurate monitoring of harmful gases and particulate matter in the environment for judging the content of pollutants in the air and controlling atmospheric pollution.